2005
DOI: 10.1111/j.1600-6143.2005.01123.x
|View full text |Cite
|
Sign up to set email alerts
|

Alemtuzumab Induction and Sirolimus Plus Mycophenolate Mofetil Maintenance for CNI and Steroid‐Free Kidney Transplant Immunosuppression

Abstract: We performed a pilot study in which 22 kidney recipients (14 LD: 8 DCD) were given alemtuzumab induction (30 mg day 0 and 1), steroids (500 mg mp day 0 and 1, none thereafter), mycophenolate mofetil (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
1
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 20 publications
2
62
1
5
Order By: Relevance
“…Incidence of acute rejection was 18.5% in SRL-TAC versus 13.5% in SRL-MMF. The efficacy of the SRL and MMF combination for the prevention of acute rejection in a steroid-free protocol was also tested using Alemtuzumab induction therapy (41). In this study, the incidence of acute rejection was 36.3%.…”
Section: Mmf and Srl Combination In Renal Transplantationmentioning
confidence: 82%
See 1 more Smart Citation
“…Incidence of acute rejection was 18.5% in SRL-TAC versus 13.5% in SRL-MMF. The efficacy of the SRL and MMF combination for the prevention of acute rejection in a steroid-free protocol was also tested using Alemtuzumab induction therapy (41). In this study, the incidence of acute rejection was 36.3%.…”
Section: Mmf and Srl Combination In Renal Transplantationmentioning
confidence: 82%
“…Flechner et al (41) showed that at 2 years a third of patients treated with SRL-MMF had normal biopsies while 79.2% of patients treated with CsA-MMF had histological evidence of CAN. Other authors found reduction of interstitial fibrosis at 3 months in patients treated with SRL-MMF versus CNI-sparing MMF (45).…”
Section: Canmentioning
confidence: 99%
“…In fact, Knechtle et al (15) using alemtuzumab and SRL found a high incidence of early humoral acute rejection. More recently, Flechner et al (44) reported the results of an immunosuppressive protocol based on alemtuzumab, SRL and MMF. They described an acute rejection rate of 36%, similar to ours, although some events were Ab-mediated.…”
Section: Discussionmentioning
confidence: 99%
“…No statistically significant difference was evident at this time point (1 year,OR 0.98,95% CI 0.28 to 3.42) or up to 5 years (5 years, OR 1.15, 95% CI 0.42 to 3.13). 115,209 l Eight studies [115][116][117]127,134,146,147,149 report on graft loss from 0.5 years to 5 years. Seven studies [115][116][117]127,134,147,149 are pooled at 1 year; however, there is no statistically significant difference between SRL + MMF and CSA + MMF (1 year, OR 1.06, 95% CI 0.44 to 2.56).…”
Section: Time To Biopsy-proven Acute Rejectionmentioning
confidence: 99%